1996
DOI: 10.1016/0167-4889(96)00031-6
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic modulation of cell growth by recombinant human galectin-1

Abstract: Human soluble galactose-binding lectin (galectin-1) has been expressed as an Escherichia coli fusion protein, following the amplification by polymerase chain reaction of cDNA prepared from a human osteosarcoma cell line. The fusion protein is a functional beta-galactoside-binding lectin, as is the recombinant galectin when purified from the cleaved fusion protein. The recombinant galectin has a biphasic effect on cell proliferation. Unlike the fusion protein, it functions as a human cell growth inhibitor, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 31 publications
8
103
0
4
Order By: Relevance
“…Other galectins also induce growth arrest. Galectin-1 functions as a cytostatic factor for murine embryo fibroblasts (12,56) and galectin-3 induces cell cycle arrest of human breast epithelial cells (14), whereas galectin-12 inhibits growth of HeLa cells (13). Galectin-3-mediated G 1 arrest involves down-regulation of cyclin E and cyclin A and up-regulation of p21 and p27 (14,57), suggesting that both galctin-8 and galectin-3 induce growth arrest by a mechanism that involves the accumulation of p21.…”
Section: Discussionmentioning
confidence: 99%
“…Other galectins also induce growth arrest. Galectin-1 functions as a cytostatic factor for murine embryo fibroblasts (12,56) and galectin-3 induces cell cycle arrest of human breast epithelial cells (14), whereas galectin-12 inhibits growth of HeLa cells (13). Galectin-3-mediated G 1 arrest involves down-regulation of cyclin E and cyclin A and up-regulation of p21 and p27 (14,57), suggesting that both galctin-8 and galectin-3 induce growth arrest by a mechanism that involves the accumulation of p21.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that galectin-1 exerts a biphasic modulation of cell growth. While high doses of galectin-1 inhibit cell proliferation independent of its sugarbinding activity, low doses of galectin-1 are mitogenic and are susceptible to inhibition by lactose (Adams et al, 1996). Furthermore, galectin-1 can also regulate cell cycle progression in human tumour cells (Wells et al, 1999).…”
Section: Galectin-1 In Tumour Growthmentioning
confidence: 99%
“…Its widespread differential expression in malignant cells and their non-transformed counterparts raises the possibility that Gal-1 also functions as a modulator of proliferation in other cell types, such as epithelial cells. Indeed, growth inhibition of tumor cells by Gal-1 has been reported (10,11). Of note, these growth effects were unaffected by the presence of a glycan inhibitor (9) or not specified with respect to glycan inhibitors (11), whereas the proapoptotic action of galectins on activated T-cells clearly depended on ␤-galactoside-specific binding (12).…”
mentioning
confidence: 97%